Answer:
The equation of the line that passes through the points
(-4,4) and (6,4)
is
y=+4
Explanation:
First of all, remember what the equation of a line is:
y = mx+b
Where:
m is the slope, and
b is the y-intercept
First, let's find what m is, the slope of the line...
The slope of a line is a measure of how fast the line "goes up" or "goes down". A large slope means the line goes up or down really fast (a very steep line). Small slopes means the line isn't very steep. A slope of zero means the line has no steepness at all; it is perfectly horizontal.
For lines like these, the slope is always defined as "the change in y over the change in x" or, in equation form:
m= y2-y1/ x2-x1
So what we need now are the two points you gave that the line passes through. Let's call the first point you gave, (-4,4), point #1, so the x and y numbers given will be called x1 and y1. Or, x1=-4 and y1=4.
Also, let's call the second point you gave, (6,4), point #2, so the x and y numbers here will be called x2 and y2. Or, x2=6 and y2=4.
Now, just plug the numbers into the formula for m above, like this:
m=0
So, we have the first piece to finding the equation of this line, and we can fill it into y=mx+b like this:
y=0x+b
Now, what about b, the y-intercept?
To find b, think about what your (x,y) points mean:
(-4,4). When x of the line is -4, y of the line must be 4.
(6,4). When x of the line is 6, y of the line must be 4.
Because you said the line passes through each one of these two points, right?
Now, look at our line's equation so far: y=0x+b. b is what we want, the 0 is already set and x and y are just two "free variables" sitting there. We can plug anything we want in for x and y here, but we want the equation for the line that specfically passes through the two points (-4,4) and (6,4).
So, why not plug in for x and y from one of our (x,y) points that we know the line passes through? This will allow us to solve for b for the particular line that passes through the two points you gave!
You can use either (x,y) point you want..the answer will be the same:
(-4,4). y=mx+b or 4=0 × -4+b, or solving for b: b=4-(0)(-4). b=4.
(6,4). y=mx+b or 4=0 × 6+b, or solving for b: b=4-(0)(6). b=4.
See! In both cases we got the same value for b. And this completes our problem.
m came out to be zero, so there is no "mx" term.